Associations Between Intention to Leave, Job Satisfaction, and Work Environment Among Registered Nurses: A Cross-Sectional Study in the United Arab Emirates - Yousef Aljawarneh PhD, MSc, BSN, RN, FHEA; Ahmad Al-Bashaireh PhD, MSc, BSN, RN; Nader E. Alotaibi PhD; Mariam Kawafha PhD; Osama Alkouri PhD; Tarfah Almesmari BSN, RN; Bashayer Alnuaimi BSN, RN; Sarah Alabdouli BSN, RN; Maryam Alsereidi BSN, RN (SAGE Open Nursing)
Objective To explore the relationships between job satisfaction, work environment, and intention to leave among registered nurses in the United Arab Emirates (UAE), and to identify potential predictors of intention to leave. Methods A cross-sectional study was conducted to collect data from registered nurses working in governmental hospitals in the UAE between October and November 2022. A convenience sampling method was used to recruit 294 participants. Results Approximately 40.8% of nurses reported a high intention to leave their jobs. Significant correlations were found between the intention to leave and several factors, including education level ( P  = .038), years of experience ( P  = .033), employment status ( P  = .002), and nationality ( P  = .037). Regression analysis revealed that both the work environment and job satisfaction were significant predictors of intention to leave (β = 1.156, P  = .015; β = 0.857, P  = .015, respectively). Conclusions The findings of this study indicate that both the work environment and job satisfaction are significant and independent predictors of nurses’ intention to leave their positions in the UAE. To reduce turnover, nursing managers and healthcare leaders should prioritize strategies that enhance work conditions, support professional development, reduce burnout, and offer competitive compensation, ultimately promoting nurse retention and better patient care.